A LONGITUDINAL STUDY OF A AUTISTIC LITTLE GIRL - Damián Díaz, Milagros; Hernandéz Corpus, Alejandra (Anales de Psicología / Annals of Psychology)
The purpose of this longitudinal study is to review the classical behaviour presented by a child having autistic traits, is mentally retarded, as from three years of age up to four, similar to that described by authors such as Kanner 1943, Wing 1981 and Frith 1991. The intervention is carried our through films in free and semi-estructured situations, both at the University s clinic and at the childs home. The results of the qualitative analysis indicate that the characteristics of the behaviour presented define the child as autistic, since serious alterations are observed in the development of communications and in her social relationships with others persons, and because of the sui generis use she makes of objects.